An Integrated approach to understand territory dynamics. The coastal alentejo (Portugal) - Lourenço, Nelson (2012)
This paper aims at presenting an integrated framework for the study of territorial dynamics in coastal areas. The use of Geographic Information Systems made possible the association of land cover data and socio-economic data using different levels of spatial analysis. The Coastal Alentejo (Portugal) was used as case study to identify these territorial dynamics.